Digital Literacy of Chinese Normal Students: A Literature Review - Jiafeng Gu (Digital Literacy for Teachers, 2022)
This article reviews Chinese academic papers from the past 20 years to investigate the digital literacy of normal students of pedagogical faculties. The main body of the article concerns “student literacy, to teacher literacy, then to normal student literacy”; regarding the theme, the context is “from digital literacy, to information literacy, then to digital information teaching ability.” Under the guidance of the Chinese education administration, the digital literacy of Chinese normal students has gradually taken on the Chinese characteristics of being practice-oriented and ability-oriented. The findings of this article are as follows: (1) In terms of research trends, the digital literacy of normal students has increased overall. This has depended on the gradual in-depth understanding of its value to the academic world, which promotes in-depth academic research while also focusing on clear and continuous policy planning. (2) In terms of research themes, the digital literacy of normal students is biased toward practice and training, and there is less research on the development of digital teaching ability in specific subjects. (3) In terms of research methods, qualitative research is still the mainstream method, but increasingly, quantitative research, including surveys, is used. (4) In terms of research results, based on the current survey report data, the digital practice ability of Chinese normal students still needs improvement. The current research has indicated the direction for the future academic community and also proposed requirements for policy researchers and makers.